Effect of chirality on the anticancer activity of Pt(ii) and Pt(iv) complexes containing 1R, 2R and 1S, 2S enantiomers of the trans-1, 2-diamino-4-cyclohexene ligand (DACHEX), an analogue of diaminocyclohexane used in oxaliplatin. Issue 43 (21st October 2021) - Papadia, Paride; Barbanente, Alessandra; Ditaranto, Nicoletta; Hoeschele, James D.; Natile, Giovanni; Marzano, Cristina; Gandin, Valentina; Margiotta, Nicola
Abstract : Two Pt(ii ) and four Pt(iv ) enantiomerically pure, oxaliplatin-like, compounds containing an unsaturated cyclic diamine as a substitute for the trans -1, 2-diaminocyclohexane used in oxaliplatin, were investigated. Abstract : Six enantiomerically pure, oxaliplatin-like, platinum compounds (two platinum(ii ) and four platinum(iv )), all containing unsaturated cyclic diamine trans -1, 2-diamino-4-cyclohexene (DACHEX) as a substitute for the trans -1, 2-diaminocyclohexane used in oxaliplatin, were investigated. The complexes were characterized by elemental analyses, ESI-MS, and 1 H-NMR spectroscopy. For the four Pt(iv ) complexes the electrochemical redox behaviour, investigated by cyclic voltammetry, showed that all complexes possess reduction potentials suitable for activation in vivo . The antiproliferative activity was assessed in vitro on human cancer cell lines, also selected for resistance to platinum-based drugs or belonging to the MultiDrug-Resistant (MDR) phenotype. All complexes exhibited antiproliferative activity superior to that of cisplatin and almost equivalent to or better than that of oxaliplatin; moreover, most complexes were also capable of overcoming both the cisplatin- and the oxaliplatin-resistance. By comparing the effectiveness of the enantiomerically pure compounds with the racemic one, the R, R enantiomer emerged as the most effective in the case of Pt(ii ) complexes whereas the S, S enantiomer was the most effective in the case of the Pt(iv ) derivatives. From the results obtained also against 3D spheroid tumor models, cis, trans, cis -[Pt(OXA)(OBz)2 (1 S, 2 S -DACHEX)] (OBz = benzoate) emerged as the most promising candidate for further preclinical investigation.